Systematic Literature Review (SLR): Sejarah dan Perkembangan Bahasa Indonesia - Ika Putri, Alifyah; Usiono, Usiono (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2025)
The Indonesian language has a long history that began with Old Malay, which served as a trade and interethnic communication language in the Nusantara archipelago since the 7th century AD. During the colonial period, Malay evolved into a formal administrative language, enriched by influences from Arabic, Sanskrit, Portuguese, and Dutch. In the 1928 Youth Pledge, Malay was officially recognized as Indonesian and designated as the language of unity, capable of bridging Indonesia's diverse ethnic and cultural backgrounds. After independence, Indonesian was established as the national and official language through the 1945 Constitution and various government standardization policies, such as the Enhanced Spelling System (EYD). This study uses the Systematic Literature Review (SLR) method to Analyze changes in the characteristic so Indonesian overtime, along with the social, political, and cultural factors influencing its development. The findings reveal that Indonesian has adapted significantly, especially during the Reform and digital eras, by incorporating foreign vocabulary and adopting a flexible, informal style. In the era of globalization, Indonesian also plays an important role in international diplomacy and the digital economy, strengthening national cultural identity both in the digital realm and within ASEAN.